Analisis Komunikasi Interpersonal Pada Aplikasi Bumble Dalam Menjalani Pertemanan - Nur Ramadhini Kautsara; Rahmadina Rahmadina (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Humans themselves are social creatures who need to interact with other people to build relationships in their daily lives. Current technological developments make it easier for us as humans to communicate interpersonally, not only directly but can be done using platforms to make friends, one of which is the Bumble application. This research aims to analyze interpersonal communication in making friends. This research uses qualitative methods with data collection techniques, namely interviews, literature study, and observation to assess the effectiveness of communication on Bumble based on five aspects of interpersonal communication according to Devito (1997): openness, empathy, support, positivity, and similarity. The research results show that these five aspects support effective communication, facilitate interaction, and strengthen connections between users, especially if there are similar interests or backgrounds. However, challenges in the form of negative behavior, such as hate speech, are still often found. In conclusion, the Bumble app can facilitate positive interpersonal communication, but requires mutual respect to build a better user experience.